After FRANCIS: next steps in the clinical evaluation of varespladib methyl. (January 2011) - Rosenson, Robert S
Secretory phospholipase A2 (sPLA2 ) represents a family of isoenzymes that participate in lipoprotein and inflammatory pathways, mediate atherosclerosis and enhance myocardial ischemic injury. The Fewer Recurrent Acute Coronary Events with Near-term Cardiovascular Inflammatory Suppression (FRANCIS) trial (NCT00743925) was a Phase II trial designed to examine the effects of varespladib methyl, a small-molecule inhibitor of sPLA2, on plasma biomarkers in patients with acute coronary syndrome (ACS) who were treated with atorvastatin 80 mg and standard-of-care daily. Varespladib methyl significantly reduced low-density lipoprotein cholesterol and inflammatory biomarkers in ACS subjects treated with standard-of-care and atorvastatin 80 mg daily. There was a nonsignificant reduction in major adverse cardiovascular events at study completion; however, positive trends remained for unstable angina and myocardial infarction. In order to achieve the widespread use of varespladib methyl in ACS patients, completion of a prospective, randomized placebo-controlled trial in ACS patients and stable coronary artery disease patients with increased sPLA2 activity will be required.